1984
DOI: 10.1530/jrf.0.0710573
|View full text |Cite
|
Sign up to set email alerts
|

Two-step freezing of two-cell rabbit embryos after partial dehydration at room temperature

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(17 citation statements)
references
References 30 publications
2
12
0
3
Order By: Relevance
“…Miyamoto & Ishibashi (1983) reported that mouse embryos survive freezing by direct transfer to subzero temperatures without seeding. The viability of directly frozen embryos depends on the degree of dehydration which can be controlled by the inclusion of sucrose in the freezing medium (Nguyen et al, 1983;Renard et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Miyamoto & Ishibashi (1983) reported that mouse embryos survive freezing by direct transfer to subzero temperatures without seeding. The viability of directly frozen embryos depends on the degree of dehydration which can be controlled by the inclusion of sucrose in the freezing medium (Nguyen et al, 1983;Renard et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Rabbit embryos have been successfully cryopreserved by conventional freezing (Bank and Maurer, 1974;Renard et al, 1984;Kojima et al, 1987;Vicente and Garcia-Ximenez, 1994) or by vitri®cation (Smorag et al, 1989;Kasai et al, 1992;Gajda and Smorag, 1993;Vicente and Garcia-Ximenez, 1994;Smorag and Gajda, 1998). Dimethylsulfoxide (DMSO), propylene glycol (PG), glycerol, or ethylene glycol (EG), alone or as mixtures, have been used as cryoprotective additives (CPAs) for freezing or for vitri®cation of rabbit embryos at the 2-cell and morula-stages.…”
Section: Introductionmentioning
confidence: 99%
“…Of 176 morulae vitri®ed in EG alone or in EG DMSO, 40% developed into blastocysts (Vicente and Garcia-Ximenez, 1994); however, of 235 morulae vitri®ed in a mixture of EG Ficoll sucrose (EFS), 89% developed into blastocysts (Kasai et al, 1992). With 2-cell-stage rabbit embryos, in vitro survival has ranged from 58% developing to blastocysts for 101 embryos vitri®ed in EFS (Smorag and Gajda, 1998), to 89% developing into morulae for 54 embryos frozen in PG (Renard et al, 1984). In contrast, these former investigators also reported that only 18% of rabbit zygotes vitri®ed in the same EFS solution developed into blastocysts.…”
Section: Introductionmentioning
confidence: 99%
“…It could even induce vitrification of the cytoplasm upon cooling (Pruli&e et al 1987;Pruli&e and Douzou 1989). Therefore, a range of studies involving both in vivo and in vitro investigations was undertaken to examine the action of 1,2-propanediol, an efficient cryoprotectant for early mammal embryos (Vincent et al 1990;Renard et al 1984;Glenister et al 1990), on actin, which is a major cytoplasmic protein.…”
Section: Introductionmentioning
confidence: 99%